Effects of mall atmosphere towards consumer behaviour during Christmas - Ong, Derek Lai Teik *; Gan, Yi Hao *; Juniaty, Iva *; Wong, Joseanne Lirn Jhet *; Ling, Ai Rick *; Subashini a/p Gullantheivello, * (2014)
Environmental elements are known to elicit stimuli to human being and consequently induce different sensations and psychological effects to a person. However when this stimuli is made of wrong balance it can hinder the positive reactions of consumers especially during festive season shopping where potentially sales are at the highest. This study examines the influence of environmental factors in a shopping mall on consumer behaviour especially during Christmas time. Convenience sampling was employed in the data collection method two months before Christmas. This study was initiated by distributing a set of questionnaires to 300 respondents in a selected shopping mall. Results were collated based on the analysis of four significant environmental variables which are interior settings, music, employee engagement and consumer density. The findings indicated that the effects of interior settings, music and employee engagement were found to be evident. Conversely, consumer density was found to elicit no effect on consumer behaviour. It was also noted that gender moderates the relationship between music and consumer behaviour. The implications of the results obtained are discussed along with the managerial implications, limitations and future researches.